Doação de sangue como prestação social alternativa - Freitas, Jayme Walmer de (2012)
This paper aims at providing guidelines for secure framework of blood donation as a punishment involving the social alternative service rendering. As of the Federal Constitution in 1988, donating blood has become a logo for many, as a way of rendering services to the community or to public entities. However, the Supreme Court has ruled to the contrary and the doctrine has adhered to such interpretation. This paper incorporates blood donation, as in the donation of food baskets, not to the list of typical restrictive penalties, but to the unnamed alternative penalties provided for in article 45, paragraph 2, of the penal law. It starts from the premise that it cannot be imposed by a final verdict of guilty, but it is the result of an agreement, of a consensus, in minor and middle potential offense infractions. For its suitability to the suggested model, it is required two or more proposals  one containing blood donation  so the perpetrator or defendant, accompanied by his/her lawyer, exercises his/her option, respecting his/her individuality